Developing cassava cultivars based on farmers needs and on the agroecological conditions of northwestern Cameroon - Christine, Z.; Richard, C.; Urs, S.; Peter, N.; Hanna, R. (2010)
Cassava is one of the most important staple food crops in Africa and has recently been gaining importance asa cash crop for smallholder farmers. The dynamics of the system requires new cultivars. The broad objectivesof the present study were (a) to specify the need for new cassava varieties; (b) determine the level of G ×E interaction in the area; (c) to suggest an effective way to select cultivars in the agro-ecologically diverseenvironment of the mid-altitudes of Central Africa. We proceeded by a farmers’ evaluation of varieties grownon-station, by a formal on-farm variety trial, and by semi-structured interviews. We found that only a fewcassava cultivars were available, given the agro-ecologically diverse nature of the area. Farmers preferrednew cultivars with a high yield, to best exploit the opportunities related to the high, mainly urban, demand forcassava processed into gari. In addition, they preferred cultivars which do not require processing other thanboiling, to break the labor peaks implicated in gari production. In the on-farm variety trial, G × E interaction isobserved to be lower in the high-potential fields (storage root yields >8.9 Mg ha-1) than in the low-potential fields(storage root yields <8.9 Mg ha-1). The present distribution pattern of local cassava cultivars was found to bebased on G × E interaction. We propose a decentralized participatory variety selection scheme to overcomethe challenges of G × E interaction in variety selection. The commonly practiced exchange of planting materialamong farmers will encourage the fast and effective dissemination of new genetic material